Promoting Human Rights standards for lesbian, gay, bisexual, and transgender people from the perspective of International law - Edison, Thomas; Liu, Chen; Hank, Tom (International Journal of Multidisciplinary Approach Research and Science, 2023)
This article examines the issue of how various religious and legal systems cope with current developments that weaken the binary opposition of men and women including their definitions of sexual identity and culture. More concretely, this book tries to explain how society and concrete laws deal with claims of lesbian, gay, bisexual, and transsexual (LGBT) who claim wider recognition. This explains the difference between the Western provisions and the policies of relevant legal bodies such as the General Assembly of the United Nations, the European Court of Human Rights, and the Supreme Court regarding this matter. This also shows the nature and real impact of international civil society forces such as the Yogyakarta principle which formulates the expansion of rights regarding lesbian, gay, bisexual, and transsexuals. Based on a comparison of various legal and religious discourses, he describes the current practice of direct and indirect discrimination and in some non-European national systems even extrajudicial killings, torture and ill-treatment, sexual assault, rape, and other human rights violations. While emphasizing the substantial differences between current European countries and non-European countries regarding policies towards lesbian, gay, bisexual, and transgender (LGBT), it points to the current trend of progress in the field by the general policy of the European Council, the most recent assessment issued by the European Court of Human Rights as well as civil society efforts such as the Yogyakarta principle. Swedish standards have been introduced to emphasize existing progressive attitudes towards LGBT people regarding gay marriage and adoption procedures.